Small Teleoperated Robot for Nuclear Radiation and Chemical Leak Detection - Kui Qian; Aiguo Song; Jiatong Bao; Huatao Zhang (International Journal of Advanced Robotic Systems, 2012)
In order to meet the actual requirements of nuclear radiation and chemical leak detection, and emergency response, a new small teleoperated robot for nuclear radiation and chemical detection is proposed. A small-size robot is manufactured according to technical requirements and the overall structure and control system is described. Meanwhile, based on the principles of human-robot interaction, a user-friendly human-robot interaction interface is designed to provide a good telepresence for the operator, helping the operator to perceive and judge the robot's situation to better assist in making the right decisions and in giving timely operation instructions. The experiment results show the robot system operates reliably and meets the technical requirements.